(untitled) (Journal of the College of Basic Education, 2023)
This study aims at (the effect of participatory learning on developing reading comprehension skills among fourth grade literary students). To achieve this, the researcher chose a sample of (60) female students from the fourth literary grade in Zainab Al-Kubra Preparatory School for Girls in Diyala Education, Al-Asri neighborhood, with (30) female students for the experimental group and (30) female students for the control group. The researcher studied the experimental group by adopting the strategies of the electronic participatory science entrance and the control group using the traditional method. of experimental designs. After the researcher identified the scientific material , which included (8) topics from the Arabic language book, which is to be taught to female students in the fourth literary grade for the academic year 2022-2023. The researcher formulated the behavioral goals of the teaching plans for the subjects, and the final number reached (115) behavioral goals, and the researcher prepared model teaching plans for each of the topics specified for the experiment, and in order to measure the reading comprehension of the students of the two research groups, the researcher prepared a reading comprehension test After applying the research tool and analyzing the results obtained by the researcher statistically, the researcher concluded that teaching by adopting the electronic participatory learning approach in the creative writing skills of the students of the fourth literary grade compared to the usual method. She recommended the necessity of adopting the electronic participatory learning approach in the reading comprehension skills of the fourth grade literary students, and the researcher suggested subsequent studies similar to the current study in the rest of the branches of the Arabic language.